Pelatihan Canva Bagi Siswa SMKS YPKP Sentani Canva Training for YPKP Sentani Vocational Students - Rahmat Nurjaman; Alienra Davry Nanda Kadun MT (BADAN PENERBIT STIEPARI PRESS, 2024)
The increasingly rapid development of information technology in the current era of globalization cannot be separated from its influence in the world of education. Current developments require the world of education to always adapt to technological developments to improve the quality of education. Office students from SMKS YPKP Sentani are the targets of this service activity. By taking the form of training, it is hoped that students can gain complete knowledge regarding the use of the Canva platform, especially to improve students' skills in using graphic design. Service outputs are in the form of publications in ISSN journals, publications in local news media and service report outputs.